FINANCIAL FEASIBILITY ANALYSIS AND MAXIMUM PROFIT OF CASSAVA AND ALOE VERA FRITTER PRODUCT (CASE STUDY AT P4S RAMA VERA) - Umi Nasyiatul Aisyah; R Hermawan; Fitria Naimatu Sadiya (Universitas Sebelas Maret, 2025)
Getuk Goreng Lidah Buaya (cassava and aloe vera fritter) were a new product from P4S Rama Vera whose feasibility and maximum profit were unknown. This study aimed to determine the financial feasibility and maximum profit that could be obtained with the available resources. The method used was mixed methods using Microsoft Excel and SPSS. Based on the results of the financial feasibility analysis, the Getuk Goreng Lidah Buaya product was declared to be feasible to be run. The results of this study state that the business is feasible because the R/C ratio is 1.30. However, the maximum profit has not been achieved. The maximum profit will be achieved at Q = 887 packs, while P4S Rama Vera still produces 678 packs for a month.